How do you solve number pattern problems through mathematical semiotics analysis and computational thinking? - Purwasih, Ratni; Turmudi; Dahlan, Jarnawi Afgani (Journal on Mathematics Education, 2024)
Some countries, including Indonesia, have a framework for understanding how students receive and process math concepts as new knowledge through learning styles. Learning style, particularly Kolb's model, is one of the learning styles that contribute to students' success in learning. Experts have explored the characteristics of Kolb's learning style and found many effects on student learning outcomes as a starting point in learning mathematical concepts. However, the research still focuses on exploring integer operation materials in specific math abilities. The researchers hardly found any discourse to study, such as exploring number patterns in computational thinking and semiotic mathematics. Therefore, this study aims to explore mathematical semiotics and computational thinking on number patterns in terms of Kolb's learning style model. This research uses hermeneutic phenomenology to explore through written tests and interviews. An explanation of the components, characteristics, and semiotic characteristics of mathematical and computational thinking seen in students who have the Kolb model of learning in solving problems of number patterns is part of the interpretation. These findings can be used as benchmarks in developing mathematics materials. Thus, this knowledge is a concrete foundation to guide future advances in curriculum, assessment methods, and learning approaches in mathematics education, particularly in algebra.